The Writing Hand and the Seated Baboon: Tension and Balance in Statue MMA 29.2.16 - Allon, Niv.
This paper offers an interpretation of statue Metropolitan Museum of Art 29.2.16 and analyzes the interplay of its two main components, the scribe and the baboon. The statue thematizes the intersection of writing, adoration and true judgment, while calling attention to points of tension between the figure of the scribe and the image of the baboon.